2017
DOI: 10.1186/s12879-017-2363-3
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of enterococci, their antimicrobial susceptibility patterns and associated factors among patients attending at the University of Gondar Teaching Hospital

Abstract: BackgroundEnterococci become clinically important especially in immune compromised patients and important causes of nosocomial infections. Data on the prevalence, antimicrobial susceptibility patterns and associated factors of enterococci are scarce in Ethiopia.MethodsA hospital based cross-sectional study was conducted at the University of Gondar Teaching Hospital from February 28, 2014 to May 1, 2014. Pretested structured questionnaire was used to collect socio-demographic data and possible associated factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
32
12
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(66 citation statements)
references
References 20 publications
20
32
12
2
Order By: Relevance
“…Regarding antimicrobial susceptibility, the current study reported high resistance rates among enterococcus isolates to a wide range of antimicrobials. These findings agree with many reports from Egypt [21,23,29] and other countries [3]. This is a serious medical challenge, as it reduces the chance of treatment, prolongs the hospital stay and increases the cost of medical care.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Regarding antimicrobial susceptibility, the current study reported high resistance rates among enterococcus isolates to a wide range of antimicrobials. These findings agree with many reports from Egypt [21,23,29] and other countries [3]. This is a serious medical challenge, as it reduces the chance of treatment, prolongs the hospital stay and increases the cost of medical care.…”
Section: Discussionsupporting
confidence: 92%
“…Enterococci are normal intestinal flora of both animals and humans, however the importance of enterococci as pathogenic bacteria has increased with the development of their resistance to multiple drugs [1,2]. Two species of enterococci have been recognized as major hospital acquired pathogens (Enterococcus faecium, "E. faecium" and Enterococcus faecalis, "E. faecalis"), particularly vancomycin resistant strains (VRE) [1,3]. VRE are multi drug resistant bacteria which can spread in hospitals through medical staff, environmental surfaces and instruments causing healthcare-associated infections that are associated with increasing mortality rates and length of hospital stay [2,4].…”
Section: Introductionmentioning
confidence: 99%
“…All of the 20 studies included in this review were crosssectional by design. Most of the studies were reported from Amhara region (n = 8) [30][31][32][33][34][35][36][37] and Addis Ababa (n = 7) [38][39][40][41][42][43][44]. The remaining studies were from Oromia (n = 4) [45][46][47][48] and Southern nations (n = 1) [23].…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…11 The prevalence of Enterococcus in wound infection in our study (38.02%) correlates with study done by Vandamme et al (37.9%) 12 and Amelework et al (25%). 13 The prevalence of Enterococcus in blood was 7.04% as compared to 4.23% and 20.8% reported in different studies. 11,13 Enterococcus faecium was found to be more drug resistant.…”
Section: Discussionmentioning
confidence: 71%